On current and future carbon prices in a risky world - Stan Olijslagers; Rick van der Ploeg; Sweder van Wijnbergen (Tinbergen Institute, 2021)
We analyse optimal abatement and carbon pricing strategies under a variety of economic, temperature and damage risks. Economic growth, convex damages and temperature-dependent risks of climatic tipping points lead to higher growth rates, but gradual resolution of uncertainty lowers them. For temperature-dependent economic damage tipping points, carbon prices are higher, but when the tipping point occurs, the price jumps downward. With only a temperature cap the carbon price rises at the risk-adjusted interest rate. Adding damages leads to a higher carbon price that grows more slowly. But as temperature and cumulative emissions get closer to their caps, the carbon price is ramped up ever more. Policy makers should commit to a rising path of carbon prices.
Keywords: H23; Q44; Q51; Q54; 330; CO2 prices; growth uncertainty; tipping points; damages; gradual resolution of damage uncertainty; temperature caps